MANAJEMEN KONFLIK PENDIRIAN RUMAH IBADAH DI KOTA PALU : (STUDI ATAS STRATEGI DAN KEBIJAKAN FKUB KOTA PALU) - Sidik, Sidik (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2024)
This research is related to managing conflict in the establishment of houses of worship in Palu City, a case study of the policies and strategies of the FKUB of Palu City. So the description is based on the problems (1) What are the strategies and policies of the FKUB in managing conflicts in the establishment of houses of worship in Palu City? (2) How effective is the strategy and policy of conflict management of the FKUB of Palu City?, (3) What are the obstacles and challenges faced in the conflict management process in Palu City? This study uses qualitative research methods through observation, in-depth interviews, and documentation studies. The data obtained were analyzed using data reduction techniques, data presentation, data verification, and conclusion—the results of the study show (1). FKUB is an institution that has the authority to manage conflicts over the establishment of houses of worship as stated in the Joint Decree of the Ministers (KBM) of Religion and Education in CHAPTER VI article 21 paragraph 2. In managing conflicts over the establishment of houses of worship in Palu City, FKUB applies strategies and policies. First, collaboration (collaborative strategy) by involving all elements of society such as village heads, RT, traditional leaders, youth leaders, LPM, Babinsa, and Babinkamtibmas. Second, effective communication (effective communication) such as in the case of the cancellation of the church house of worship on Jalan Tanjung Balantak, South Lolu Village by gathering all the people and communicating with the mayor. So that the conflict can be resolved and there is no physical clash between the local community. Third, government regulatory policies (public policy) with the Joint Decree of the Ministers no. 8/9 which regulates the provisions and requirements for the establishment of houses of worship and also regulates the pattern of conflict handling, so that these provisions can provide stability to the diverse society in Palu City. (2). The effectiveness of the strategy and policy of the Palu City FKUB in the management and administration of the conflict over the establishment of houses of worship in Palu City can be seen from its success in managing the conflict by always providing recommendations for the establishment of houses of worship. (3). Meanwhile, the obstacles and challenges of Palu City FKUB as an institution authorized to handle the conflict over the establishment of houses of worship does not experience many obstacles and challenges because the people of Palu City have a high tolerance for religious diversity. Contribution/Benefits: From the findings of the study on conflict management in the establishment of houses of worship, a study of policies and strategies of the Palu City FKUB. The Palu City FKUB applies a strategy of collaboration, and accommodation communication and implements the Joint Decree of the Minister of Religion and Home Affairs (KBM) No. 8/9. The Palu City FKUB in carrying out conflict management uses a preventive approach or preventive measures such as conducting socialization and counseling on the requirements for building houses of worship. The contribution of this research for the FKUB is strengthening the conflict resolution policy or after the conflict occurs because the results of this study, the Palu City FKUB only handles conflicts before the conflict occurs (preventive management). For academics, this study provides a concrete picture of the dynamics of the construction of houses of worship in the City of Palu which can be used as a comparison with research in other areas or comparing conflict strategies in other cities. For the community, it provides an understanding of the importance of interfaith dialogue to maintain social harmony and make the community aware of the role of the FKUB as a facilitator who can bridge differences.